Caregiver overload syndrome among workers of shelters in North of Lima - Vargas, Selene (2019)
Objective: Determine the frequency of the caregiver syndrome among workers of shelters in North of Lima. Materials and methods: Transversal descriptive study. The sample consisted of 143 workers of both genders, dedicated to the care of the elderly. The data collection was developed between November and December 2017. The instrument used was the Zarit scale. Results: The average age of the participants was 40 years (SD = 13.6, min 18, max. 64), 72.7% (n = 104) of the caregivers were women, with a predominance of the age group of 18 at 30 years with 32.9% (n = 47), 60. 2% (n=86) were married or cohabitant. Regarding the work characteristics, 58% (n = 83) of the caregivers worked in the morning shift, 67.1% (n = 96) had no family ties with the patient, 42.7% (n = 61) were dedicated to the care of the patient between 1 to 3 years and 74.8% (n = 107) were responsible for care between 1 to 5 older adults. Regarding the level of overload, 96.5% (n = 138) resulted in heavy overload and 3.5% (n = 5) with slight overload. Conclusion. All the caregivers of the older adult living in the shelters located in North zone of Lima, presented overload, with a high proportion of intense overload, mainly in the female gender.